2021
DOI: 10.1108/lhtn-05-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things in contemporary academic libraries: application and challenges

Abstract: Purpose Academic libraries are constantly adopting emerging technologies to deliver innovative services. A recent trend in technological innovation is the Internet of Things (IoT). Consequently, this study theoretically x-rayed the various ways in which IoT could be applied to academic libraries and the expected challenges associated with the adoption of the technology. Design/methodology/approach This study used the review method to examine the application of IoT in contemporary academic libraries. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…However, empirical evidence from developing countries like Nigeria and Pakistan show that IoT applications in university libraries are mostly restricted to smart circulation systems, RFID-based security control, and theft management (Eiriemiokhale and Olutola, 2023;Asim et al, 2022). The implementation of innovative IoT technologies in libraries can improve management effectiveness, make libraries smarter, protect library resources, improve readers' service, save users' time, reduce the cost of library maintenance and enhance staff competency (Xu, 2022;Igbinovia and Okuonghae, 2021a).…”
Section: Iot Applications In Librariesmentioning
confidence: 99%
See 4 more Smart Citations
“…However, empirical evidence from developing countries like Nigeria and Pakistan show that IoT applications in university libraries are mostly restricted to smart circulation systems, RFID-based security control, and theft management (Eiriemiokhale and Olutola, 2023;Asim et al, 2022). The implementation of innovative IoT technologies in libraries can improve management effectiveness, make libraries smarter, protect library resources, improve readers' service, save users' time, reduce the cost of library maintenance and enhance staff competency (Xu, 2022;Igbinovia and Okuonghae, 2021a).…”
Section: Iot Applications In Librariesmentioning
confidence: 99%
“…Despite the opportunities of IoT, some studies identified a number of challenges of implementing IoT technology in libraries (Asim and Arif, 2023;Asim et al, 2022;Harati et al, 2021;Igbinovia and Okuonghae, 2021a;Bansal et al, 2018;Kaba and Ramaiah, 2019;Kumar, 2016;Hoy, 2015). As there is no standard for this technology, it can exchange data using multiple companies' own parameter and thus the risk of unauthorized access and system hacking would be a common issue (Hoy, 2015).…”
Section: Challenges Of Iot Adoption In Librariesmentioning
confidence: 99%
See 3 more Smart Citations